The Effect of Phosphogypsum on Reducing CO2, CH4, and NH3 Emissions During Composting of Cattle Feedlot Manure: Comparing Aerobic and Anaerobic Composting - Chu, Angus; Talaei, Mohammad Reza (Journal of Environmental Treatment Techniques, 2025)
Phosphogypsum (PG) amendments have been explored as a strategy to enhance composting efficiency while mitigating greenhouse gas emissions and nitrogen losses. This study investigated the effects of PG at different concentrations (3%, 8%, and 15%) on cattle manure composting under both aerobic and anaerobic conditions over a 14-day period. The results indicate that PG significantly influenced gas emissions, nitrogen transformation, and compost maturity. Under aerobic conditions, CO₂ emissions increased rapidly during the initial phase, reflecting active microbial respiration, whereas anaerobic composting exhibited lower CO₂ emissions, indicating slower decomposition. Methane (CH4) emissions were significantly reduced with PG, with complete suppression at 8% and 15% PG under anaerobic conditions, likely due to competition between sulfate-reducing bacteria and methanogens. Ammonia (NH₃) emissions also decreased with increasing PG levels in both systems, suggesting improved nitrogen retention through ammonium adsorption and pH regulation. However, compost maturity was delayed in PG-treated samples, as indicated by lower NO₃⁻-N accumulation and prolonged ammonium presence. These findings suggest that PG amendments can effectively reduce greenhouse gas emissions and enhance nitrogen retention, making them a viable strategy for sustainable manure management. However, longer composting durations or optimized aeration strategies may be necessary to achieve full stabilization. Future research should explore the longterm impacts of PG-enriched compost on soil health and plant growth to maximize its agronomic potential.